Trithiocarbonates as intrinsic photoredox catalysts and RAFT agents for oxygen tolerant controlled radical polymerization. Issue 9 (3rd February 2017) - Fu, Q.; Xie, K.; McKenzie, T. G.; Qiao, G. G.
Abstract : In this study, we reported on the discovery that trithiocarbonates (RAFT agents) can act as intrinsic photocatalyst to significantly reduce the oxygen level in a controlled radical polymerization under visible light irridation. Abstract : This study reports the discovery that trithiocarbonate RAFT agents can significantly reduce the amount of dissolved oxygen when irradiated with visible light ( λ max ≈ 460 nm) in the presence of a sacrificial tertiary amine. By taking advantage of this effect, we conducted a series of photo-CRPs of acrylates without the requirement of pre-degassing the reaction mixtures. In these systems, the trithiocarbonate plays a triple role of photocatalyst for oxygen removal, initiator, and RAFT agent for polymerization control. We believe this robust and facile synthetic method will be beneficial for cost-effective industrial applications as well as the laboratory-scale synthesis of functional polymeric materials.